GROWTH RESPONSE OF CLOWN LOACH (Chromobotia macracanthus Bleeker 1852) JUVENILES IMMERSED IN WATER CONTAINING RECOMBINANT GROWTH HORMONE - Asep Permana; Alimuddin Alimuddin; Wartono Hadie; Agus Priyadi (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
The main problem in the culture of clown loach (Chromobotia macracanthus) is the slow growth rate, which takes about six months to reach its market size (two inches total body length). Slow growth eventually cause a long production time and increase the production costs. An alternative solution can be proposed in order to enhance the growth is by using recombinant growth hormone. The aim of this study was to determine the immersion dose of recombinant Epinephelus lanceolatus growth hormone (rElGH) which can generate the highest growth in clown loach. Larvae at seven day after hatching were hyperosmotic treated with NaCl 2.0% for one minute, then immersed for one hour in water containing 0.3% NaCl, 0.01% bovine serum albumin (BSA), and different doses of rElGH, namely: 0.12 (treatment A), 1.2 (B), 12 (C), and 120 mg/L (D). As control, fish were immersed in water without rElGH and NaCl (control-1), water containing 0.3% NaCl and 0.01% BSA (control-2), and 0.3% NaCl water (control-3). Each treatment was replicated three times. The results showed that clown loach juveniles in treatment B, C, and D had longer total body length (P<0.05) than control-1, while fish treatment A was the same as controls. Survival and body weight were similar in all treatments and controls (P>0.05). In addition, the percentage of large size juveniles increased approximately 5% in treatment B, almost the same as in the medium size, while the small size were decrease compared to the control-1. Thus, the best immersion dose of rElGH was 1.2 mg/L water.